Trait Emotional Intelligence and Relationship Satisfaction: The Mediating Role of Dyadic Coping. Issue 1 (2nd January 2020) - Wollny, Anna; Jacobs, Ingo; Pabel, Luise
Abstract: Trait emotional intelligence ( TEI ) is an important individual difference variable that is related to the quality of romantic relationships. The present study investigated the associations between TEI, dyadic coping, and relationship satisfaction. A convenience sample of N = 136 heterosexual couples was recruited online. When the actor-partner interdependence model was applied to the data, TEI showed a positive actor effect and a positive partner effect on relationship satisfaction. The actor effect and partner effect of TEI on relationship satisfaction were partially mediated through positive dyadic coping and common dyadic coping, respectively. A small total indirect actor effect was also found for negative dyadic coping. Controlling for potential content overlap between TEI and relationship satisfaction did not alter the results. However, removing variance from the TEI score that was shared with the Big Five trait factors attenuated TEI's actor and partner effects on relationship satisfaction and rendered all but one actor effect for TEI on dyadic coping and all but one indirect effect nonsignificant. The results underline the importance of TEI for the quality of romantic relationships and they shed light on underlying mechanisms. Implications for theory, research, and applications in counseling contexts will be discussed.